Distribution of Temperature and Total Suspended Solids (TSS) Of Lake Buyan Water Based On Pan-Sharpening Landsat 8 Data - Tolhas Tomu Tumeang; I Made Yuliara; I Gde Antha Kasmawan (Buletin Fisika)
This research aims to compare the distribution of temperature and Total Suspended Solid (TSS) of water using laboratory test data and Landsat 8 satellite imagery at Lake Buyan by applying the Pan-Sharpening method. Landsat 8 image data from various bands, including bands 2, 3, 4, 5, 8, 10, and 11 are used to analyze the spatial distribution of physical parameters of temperature and TSS. The research results show that the highest temperature distribution is in band 10 at the 27th point and band 11 at the 25th point. The lowest temperature was recorded at the 1st and 2nd points, each at 25.00 0C, while the highest temperature was at the 28th to 30th points with a value of 26.00 0C. Analysis of the correlation between Landsat 8 data and in situ data produces a strong positive correlation for band 10 (0.7005) and a strong negative correlation for band 11 (0.4602). However, the Root Mean Square Error (RMSE) value for temperature in band 10 is 5.54 and in band 11 is 5.59, indicating a poor level of accuracy. Factors such as weather and the presence of clouds can influence the rise and fall of surface temperatures, causing temperature calculation results to be not optimal. The results of this research show the limitations of using Landsat 8 satellite data in monitoring temperature and TSS in Lake Buyan.